Pembelajaran Bahasa Indonesia bermuatan Ecopedagogis untuk Meningkatkan Kecerdasan Ekologis - Nur Samsiyah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Ecological intelligence needs to be taught from elementary school age in order to have awareness of the environment. The aim of this research is to describe Indonesian language learning with eco pedagogical content to increase ecological awareness. The research method uses descriptive qualitative. The research subjects were 15 grade 5 students at SDN Bulu 3 Madiun. Data collection techniques were tests and observations. Data is analyzed by reviewing observation data, reduction by sorting data, presentation by organizing data, and data reduction. The results of the research show that environmental material in Indonesian language learning takes the form of caring for the environment and caring for waste. The observation results show that ecological awareness is in the high category with a score of 4. The implementation of Indonesian language learning has educational content, obtaining recycled products, posters, and observation reports. Meanwhile, the Indonesian language proficiency test results obtained an average of 78.